PERBEDAAN LAMA PENYINARAN UV-C TERHADAP REDUKSI JUMLAH ESCHERICHIA COLI PADA AIR BERSIH DAPUR PT. XYZ (Politeknik Kesehatan Kemenkes Bandung, 2021)
Kitchen clean water at PT. XYZ is used for washing activities and also washing all cooking utensils. The clean kitchen water is indicated to contain Escherichia coli bacteria as much as 71 APM/100 ml and exceeds the applicable quality standards. For this reason, further treatment of clean water is needed by means of disinfection, the disinfection used is Ultra Violet-C light with a wavelength of 254 nm because it is germicidal for bacteria. The purpose of this study was to find out and analyze the duration of Ultra Violet-C irradiation that was most effective in reducing Escherichia coli bacteria. This type of research is an experimental research with a pretest posttest without control research design using clean kitchen water samples with 2 variations of irradiation time, namely 55 seconds and 85 seconds. Statistical testing using the Mann Whitney test resulted in a P value of 0.146 which indicated that there was no significant difference between 55 seconds and 85 seconds of Ultra Violet-C irradiation for reducing the number of Escherichia coli bacteria. The average percentage decrease in Escherichia coli bacteria at 55 seconds of irradiation is 99.85%, while at 85 seconds of irradiation is 100%. The most effective UV-C irradiation time in reducing Escherichia coli bacteria in clean water from the kitchen of PT. XYZ is 85 seconds long.